2019
DOI: 10.1038/s41598-019-52098-5
|View full text |Cite
|
Sign up to set email alerts
|

Studying electronic properties in GaN without electrical contacts using γ-γ vs e−-γ Perturbed Angular Correlations

Abstract: The potential use of combined e−-γ vs γ-γ Perturbed Angular Correlations (PAC) experiments as a possible alternative to study electronic properties of materials and/or samples where Hall effect measurements are difficult to perform due to low-quality ohmic contacts is here demonstrated using Si- and Zn-doped GaN samples as a showcase example. To do so, the lattice site of implanted 181Hf/181Ta and the recombination of Ta ionized and excited electronic states were studied as a function of temperature and sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…The degree to which the e−γ and γ−γ TDPAC signals differ from each other depends on the timescale (and hence speed) of the host material to provide its recombination electrons to the TDPAC nuclear probe following internal conversion of the excited 181 Ta to ground state 181 Ta as a TDPAC probe (Further details are contained in Section 2). This is wonderfully demonstrated in the recent 181 Ta(GaN) TDPAC experiment by Barbosa et al [31], where they have performed a temperature-and "Si-and Zn-dopant" concentration-dependent study. In Figure 1 of the corresponding paper, they had shown that their e−γ signals differ from those of the corresponding γ−γ signals.…”
Section: Motivation For Applying the E−γ Tdpac Spectroscopy To The Ti...mentioning
confidence: 91%
See 1 more Smart Citation
“…The degree to which the e−γ and γ−γ TDPAC signals differ from each other depends on the timescale (and hence speed) of the host material to provide its recombination electrons to the TDPAC nuclear probe following internal conversion of the excited 181 Ta to ground state 181 Ta as a TDPAC probe (Further details are contained in Section 2). This is wonderfully demonstrated in the recent 181 Ta(GaN) TDPAC experiment by Barbosa et al [31], where they have performed a temperature-and "Si-and Zn-dopant" concentration-dependent study. In Figure 1 of the corresponding paper, they had shown that their e−γ signals differ from those of the corresponding γ−γ signals.…”
Section: Motivation For Applying the E−γ Tdpac Spectroscopy To The Ti...mentioning
confidence: 91%
“…Their e−γ TDPAC spectrometer was significantly upgraded later and brought to its full capacity at the Solid-State Physics ISOLDE-CERN facility in the early 1990s [42][43][44]. Recent experiments using the modern e−γ TDPAC spectrometer include a temperature-and "Si-and Zn-" dopant concentrationdependent study on 181 Ta(GaN) [31], which provides signals related to the recombination process and with the help of simulations based on DFT. On this basis, researchers ascribe this phenomenon to variable-range hopping in the low-temperature regime and thermally mobile electrons (electrons in the conduction band) in the high-temperature regime.…”
Section: Isolde-cernmentioning
confidence: 99%